The place of translation in teaching Turkish as a Foreign language - (:unkn) unknown (Peter Lang AG, 2018)
This study covers the use of translation activities, one of the many activities that have been used in language teaching from past to present in teaching Turkish as a foreign language. Translation is divided into two aspects by scholars: pedagogical translation and real translation. What we focus on is the former, which is used as a means. The study continues by highlighting specific points related to the teaching of Turkish as a foreign language based on the place of translation in language teaching in general. The first section of this two-section study discusses the place of translation in language teaching and the second section focuses on teaching translation courses and the practice of translation activity. As a result of the study, it can be understood that translation activities can be used effectively in teaching Turkish as a foreign language, and the four basic language skills can be developed by means of translation activities. © Peter Lang GmbH.
Keywords: Pedagogical translation; Real translation; Teaching turkish as a foreign language; Translation